PENGARUH HOSPITALISASI TERHADAP TINGKAT KECEMASAN ANAK PRESCHOOL DI RUMAH SAKIT TK II PUTRI HIJAU KESDAM I/BB MEDAN - Khairani, Ade Irma; Olivia, Nina (Jurnal Riset Hesti Medan, 2018)
Sick children have a different response in which the child has unusual anxiety by interacting with other people, it causes the child must undergo hospitalization. In Indonesia an estimated 35% of children undergoing hospitalization and 45% had anxiety. The purpose of this study was to determine the effect of hospitalization on the level of anxiety of preschool children in child inpatient hospital TK II Putri Hijau Kesdam I/BB city of Medan. This type of research is analytic survey with cross sectional design. The population in this study across Preschool children who were treated at the TK II Putri Hijau Kesdam I/BB Medan with the average monthly total of 35 patients. Samples used as many as 20 people using total sampling technique. The data were obtained using a questionnaire and analyzed by using Spearman Rank Test (Rho). The test results Spearman Rank (Rho) with the results obtained α = 0.05 p value = 0.001 (p value <α 0.05) and the correlation coefficient (ρ) with a value of -0.502 which can be concluded that there are significant and not the direction being between hospitalization support the preschool child's anxiety level. Thus, the better the hospitalization, the lower the anxiety levels of preschool children. It is expected that health professionals in order to work professionalism to achieve optimum service and maximum.Keywords: Hospitalization, Anxiety Levels, Preschool Children